2017
DOI: 10.1615/intjmedmushrooms.2017021162
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Virtual Screening Analysis of Lanosterol Derivatives from Ganoderma Medicinal Mushrooms (Agaricomycetes) as Selective Ligands of Human Androgen Receptor

Abstract: Male sex hormones such as testosterone and dihydrotestosterone play important roles in several physiological and pathological processes. The biological activities of the aforementioned metabolites are mediated by the multidomain androgen receptor (AR), which is therefore a well-studied drug target. Ganoderma mushroom lanostanoid extracts have previously been shown to exert antiandrogenic activity; therefore, this work aims to identify which lanostane derivatives might act as selective ligands for AR. Because p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…El uso de tres confórmeros distintos por cada mutante del AR estudiada permite explorar la flexibilidad conformacional del sistema, brindando resultados más robustos durante el análisis de acoplamiento molecular. 13,22 La energía libre de acoplamiento calculada para cada sistema ligando-receptor se resume en la Tabla 2. Los valores de energía libre de acoplamiento calculados para el AR de fenotipo silvestre (WT) y la mutante (T878A) fueron comparados mediante una prueba Wilcoxon-Mann-Whitney, y se encontraron diferencias estadísticamente significativas entre ambos (p<0.01).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…El uso de tres confórmeros distintos por cada mutante del AR estudiada permite explorar la flexibilidad conformacional del sistema, brindando resultados más robustos durante el análisis de acoplamiento molecular. 13,22 La energía libre de acoplamiento calculada para cada sistema ligando-receptor se resume en la Tabla 2. Los valores de energía libre de acoplamiento calculados para el AR de fenotipo silvestre (WT) y la mutante (T878A) fueron comparados mediante una prueba Wilcoxon-Mann-Whitney, y se encontraron diferencias estadísticamente significativas entre ambos (p<0.01).…”
Section: Resultsunclassified
“…4,5 En ese sentido, es interesante notar que es precisamente la DHT el ligando con menor energía libre de acoplamiento calculada para dicho receptor (-6.100 ± 1.957 kcal/mol). Se sabe que el modo de unión característico entre la DHT y el AR de fenotipo silvestre implica la formación de un enlace de hidrógeno entre el grupo hidroxilo presente en C17 de la DHT y la T878, 13,23,24 el cual fue posible detectar en nuestro estudio (Figura. 4).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Even in silico studies have demonstrated their antiproliferative effects through the interaction with nuclear receptors such as the vitamin D receptor, diminishing the cell growth and activating cell differentiation [ 54 ]. The androgenic outcomes of lanostanoids have been indicated by another in silico analysis explaining the affinity between the C3- ketonic group of the triterpenes and the androgen receptor belonging to the nuclear receptor superfamily [ 55 ]. All of the abovementioned reports explain the high bioactivity scores that all of the isolated secondary metabolites expressed in the in silico study of the present research.…”
Section: Discussionmentioning
confidence: 99%